(untitled) (Manila, 1995)
The Asian Fisheries Society (AFS) is a non-profit scientific society founded in 1984 by fishery professionals in Asia. The society aims at promoting networking and co-operation between scientists, technicians and all stakeholders involved in fisheries (including aquaculture) production, research and development in Asia. Its ultimate objective is to enhance food security and income generating opportunities for fisheries workers via sound management practices, environmentally sustainable development and efficient utilization of the aquatic resources.
Keywords: Fisheries,Bibliograhy; Research; Asia